IL-21 arming potentiates the anti-tumor activity of an oncolytic vaccinia virus in monotherapy and combination therapy - Xiaoyan Zhang (BMJ Publishing Group, 2021)
Background Oncolytic viruses (OVs) have shown promise in containing cancer progression in both animal models and clinical trials. How to further improve the efficacy of OVs are intensively explored. Arming OVs with immunoregulatory molecules has emerged as an important means to enhance their oncolytic activities majorly based on the mechanism of reverting the immunosuppressive nature of tumor environment. In this study, we aimed to identify the optimal combination of different OVs and immunomodulatory molecules for solid tumor treatment as well as the underlying mechanism, and subsequently evaluated its potential synergy with other immunotherapies.Methods Panels of oncolytic viruses and cells stably expressing immunoregulatory molecules were separately evaluated for treating solid tumors in mouse model. A tumor-targeted replicating vaccinia virus Tian Tan strain with deletion of TK gene (TTVΔTK) was armed rationally with IL-21 to create rTTVΔTK-IL21 through recombination. CAR-T cells and iNKT cells were generated from human peripheral blood mononuclear cells. The impact of rTTVΔTK-IL21 on tumor-infiltrating lymphocytes was assessed by flow cytometry, and its therapeutic efficacy as monotherapy or in combination with CAR-T and iNKT therapy was assessed in mouse tumor models.Results IL-21 and TTV was respectively identified as most potent immunomodulatory molecule and oncolytic virus for solid tumor suppression in mouse models. A novel recombinant oncolytic virus that resulted from their combination, namely rTTVΔTK-mIL21, led to significant tumor regression in mice, even for noninjected distant tumor. Mechanistically, rTTV∆TK-mIL21 induced a selective enrichment of immune effector cells over Treg cells and engage a systemic response of therapeutic effect. Moreover, its human form showed a notable synergy with CAR-T or iNKT therapy for tumor treatment when coupled in humanized mice.Conclusion With a strong potency of shaping tumor microenvironment toward favoring TIL activities, rTTVΔTK-IL21 represents a new opportunity worthy of further exploration in clinical settings for solid tumor control, particularly in combinatorial strategies with other immunotherapies.One sentence summary IL21-armed recombinant oncolytic vaccinia virus has potent anti-tumor activities as monotherapy and in combination with other immunotherapies.